Cattle growth hormone and leptin genes influence on fattening traits - Miceikien?, Ilona; Pe?iulaitien?, Nijole; Mak?tutien?, Natalija; Baltr?nait?, Lina; Mork?nien?, Kristina; Liucvaikien?, Kristina; Mi?eikien?, Ramut? (Cuban Journal of Agricultural Science, 2013)
This article presents data about growth hormone and leptin gene polymorphism and its influence on cattle fattening traits. A total of 163 animals were genotyped, belonging to the breeds Lithuanian Black and White (LBW), Lithuanian Red (LR), Hereford (HE), Limousin (LI), Simmental (SI), and Charolais (CH). The records of daily weight gain were obtained from the feeding control station of ?ilut? bulls feeding. The research method of polymerase chain reaction (PCR) and restriction length polymorphism (RFLP) were used to GH and LEP genotype polymorphisms. In the control group, the growth hormone gene allele A was found, with maximum frequency (0.875) in Simmental breed, and allele B (0.283) in the Lithuanian Red breed. Similarly, Leptin gene allele A was found with maximum frequency (0.875) in Simmental breed, and allele B (0.283) in the Lithuanian Red breed. The AA genotype growth hormone, with the highest frequency of 90%, was found in Hereford cattle, AB genotype in 34.8 % of Lithuanian Red and BB genotype in 37.5 % of the Simmental genotype. While, the leptin gene AA genotype with the highest frequency, was found in Simmental and Limousin cattle, AB genotype in the Charolais and BB genotype in Lithuania Red cows. The research on genetic effects on the weight gain of animals in different fattening periods showed that the leptin gene had a significant influence on the weight gain during the first two fattening quarters. Leptin gene varied from 0.1 to 4.4 %. Leptin gene A allele increased cattle weight gain. Cattle with AA genotype growth hormone had the greatest weight gain, but the differences were not statistically significant. Key words: cattle; growth hormone, leptin gene.